Evaluation of drying techniques on nutritional and volatile components of Bombay red onion (Allium cepa) - DEMISSEW, AYALEW; MERESA, AYENEW; TEMESGEN, KIBER (The Indian Journal of Agricultural Sciences, 2019)
In this study performance of three drying methods on nutritional and important volatile components of red onion were evaluated. Onion (Allium cepa L.) is a strong-flavoring vegetable consumed in different ways, mainly due to its distinctive flavor or, simply pungency. The shelf-life of fresh onion bulbs are short enough about two weeks at ambient storage conditions in Fogera district, Amhara region, Ethiopia. This is mainly due to the presence of high moisture in fresh onion bulbs. Postharvest loss of onion bulbs also reaches up to 50% in the production season in Fogera district. Consequently, onion bulbs had extremely variable market price during production and off-season in the district, which directlyinfluences both growers and consumers. The effects of different drying techniques on protein, carbohydrate, total sugar, fat, pyruvic acid, ascorbic acid, total phenol, total flavonoid, rehydration ratio, colour, and sensory properties of onion slice were evaluated and found insignificant at P> 0.05 for microwave and modified direct solar dryers, taking fresh onion bulbs as the control. However, oven drying methods had a significant effect on onion physicochemical quality attributes at P